PERFORMANCE ANALYSIS OF E-COMMERCE COMPANIES USING BALANCED SCORECARD IN THE INDONESIA STOCK EXCHANGE DURING 2022–2023 - Dewani, Safana Aura; Rois, Muhammad; Winarni (Journal of Indonesian Applied Economics, 2025)
Purpose This study is to analyze the performance of e-commerce companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2023 using the Balanced Scorecard (BSC) approach. Design/methodology/approach The study employs a descriptive applied quantitative methodology, analyzing financial data to address business phenomena and assess their impact on company performance. Findings The findings indicate a consistent decline in performance across the studied companies. In 2022, the average performance score was 51%, categorized as less healthy (BBB), which dropped to 41% (BB, less healthy) in 2023. Specifically, PT Bukalapak.com Tbk's performance declined from 61% (BBB) in 2022 to 48% (BB) in 2023, PT GoTo Gojek Tokopedia Tbk decreased from 51% (BBB) to 38% (B), and PT Global Digital Niaga Tbk fell from 41% (BB) to 38% (B). These results highlight the need for improved financial strategies and operational efficiencies to enhance the financial health of Indonesian e-commerce companies. Research limitations/implications The research is limited by the use of only the Balanced Scorecard method, the lack of indicators in perspectives other than finance, and the absence of an in-depth SWOT analysis. Originality/value This study lies in its focus on analyzing the performance of e-commerce companies listed on the IDX from 2022 to 2023 using the Balanced Scorecard approach, which provides valuable insights into the financial health and operational challenges faced by these companies during a period of significant market changes.